(untitled) (Eurasian Medical Research Periodical, 2026)
The article presents a comparative study of laboratory indicators in patients undergoing hemodialysis following complex treatment procedures. The results demonstrate that during renal replacement therapy, patients continue to experience deficiencies in hemoglobin, albumin, calcium, and vitamin D. Conversely, the study shows persistently elevated levels of leukocytes, urea, creatinine, parathyroid hormone, and fibroblast growth factor-23 in the blood serum. These findings emphasize the necessity of an individualized approach to addressing these issues for each patient.